Control of human limb movements: The leading joint hypothesis and its praktical applications - Dounskaia, N. (Exercise and Sport Sciences Reviews, 2010)
The leading joint hypothesis (LJH) offers a novel interpretation of control of human movements that involve multiple joints. The LJH makes control of each multijoint movement transparent. This review highlights effective applications of the LJH to learning of new motor skills and to analysis of movement changes caused by aging and motor disorders.